Haggai - Wolff, Hans Walter; (1911-1993) (U.S.A, 1988)
In this distinguished commentary, Wolff is concerned to defend Haggai as much more than a (3z(Bminor(3y (Bprophet. He was a man whose feet were placed firmly on the ground, one of the dominating figures of the postexilic community, the main instigator of the rebuilding of Jerusalem temple, and so responsible for inaugurating a new era in Jewish history.s
Keywords: Bible -- Haggai